Alternative teaching behaviour management strategies for children with autism: An Approach based on functional behavioral assessment - Sukinah, Sukinah; Taqiyah, Dewi Barotut (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
This study aimed to investigate effective behavior management strategies for children on the autism spectrum using a Functional Behavioral Assessment (FBA) approach. Research highlights behavioral challenges exhibited by children with autism. These include difficulties with social interaction, communication deficits, sensory sensitivities, repetitive behaviors, and resistance to change. The research focused on a single child with autism, aged six years 11 months, identified as DT. This study used a case study research with a qualitative approach involving data collection through observation, interviews, and document analysis. The results show that the FBA approach can provide a comprehensive understanding of the factors that influence the behavior of children with ASD. Behavior management strategies based on FBA consist of identifying individual needs, developing appropriate intervention programs, and ongoing monitoring for promoting individualized interventions, early intervention, effective teaching practices, and evidence-based practice. Keywords: teaching behavior management, children with autism, functional behavior assessment.